Cultural terms and the translation strategies in Tilik short movie English subtitle (Diksi, 2022)
The aims of this research are to identify and describe the categories of cultural vocabulary as well as the strategies used in translating those vocabulary into English found in a Tilik short movie subtitle. In addition, this research also aims to identify and describe the equivalent alternatives found in this short movie. The data that are used in this study is a short movie entitled Tilik. The findings indicate that there are four translation strategies used by the translators. From the analysis, it is found that the most used translation strategy in translating cultural terms in short movie Tilik is functional equivalent, followed by cultural equivalent reduction and additional explanation. Keywords: cultural terms, strategies of translation